THE SKIN IRRITATION RISK OF CHILI FRUIT NANO GEL ON EXPERIMENTAL RABBIT SKIN - Phan, Hong Minh (Tạp chí Sinh lý học Việt Nam, 2024)
Chili is not only a popular spice in food preparation but is also used as a traditional medicine. In particular, when used topically, the active ingredient called capsaicin in chili peppers helps treat bone and joint pain. Objectives: The study aims to evaluate the local irritation on the healthy skin of rabbits of a nano gel product containing chili fruit extract provided by the Institute for Applied Research of Traditional Medicine. Methods: The study was conducted according to the guidelines of the Vietnam Ministry of Health, ISO 10993-10, and OECD on skin irritation assessment for topical products. Three healthy white New Zealand rabbits were used. Animals were applied gauze which was soaked in nano gel containing chili fruit extract at a dose of 0.5 grams on a healthy skin area 2.5 x 2.5 cm for 4 hours. We evaluated the irritation index including erythema and edema on the skin at 24, 48, and 72 hours after gauze removal. Results: Three rabbits were still healthy, and living normally, there were no signs of erythema and edema on the rabbit's skin, and the irritation indexes were 0 during 72 hours of continuous monitoring. Conclusion: The nano gel containing chili fruit extract applied topically does not irritate healthy rabbit skin.